Q. 19

# If y = (tan ^{- 1} x)^{2}, show that (x^{2} + 1)^{2}

Answer :

Given; y = (tan ^{- 1} x)^{2}

Hence Shown

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

If y = tan^{-1}x, find in terms of y alone.

If y = sin^{-1} x, show that

If y = 3 cos(log x) + 4 sin(log x), show that

Mathematics - Board Papers

If x = t^{2}, y = t^{3}, then is

If x = a cos θ + b sin θ, y = a sin θ – b cos θ, show that

Mathematics - Board PapersIf prove that

Mathematics - Exemplar

If y =(tan^{–1}x)^{2}, show that

If y = (tan ^{- 1} x)^{2}, show that (x^{2} + 1)^{2}